Constraints on the evolution of resistance to gall flies in Solidago altissima: resistance sometimes costs more than it is worth. Issue 1 (8th May 2017) - Wise, Michael J.; Abrahamson, Warren G.
Summary: Plant populations frequently maintain submaximal levels of resistance to natural enemies, even in the presence of substantial genetic variation for resistance. Identifying constraints on the evolution of increased resistance has been a major goal of researchers of plant–herbivore interactions. In a glasshouse study, we measured relative costs and benefits of resistance of tall goldenrod ( Solidago altissima ) to the gall‐inducing tephritid Eurosta solidaginis . We exposed multiple ramets of 26 goldenrod genets to nutrient or shade stress and to oviposition by E. solidaginis . The presence of a gall cost a ramet an average of 1743 seeds, but the cost differed 10‐fold across environments. Plant genets varied widely for an induced 'hypersensitive' response in which meristem cells become necrotic and kill E. solidaginis hatchlings before gall induction. There was no evidence that this highly effective resistance trait carried an allocation cost. However, the response carried a risk of autotoxicity, as necrosis killed the apex of 37% of the ungalled ramets. On average, a damaged apex cost each ramet 5015 seeds. Autotoxicity may constrain the resistance of S. altissima to an intermediate level, and variation in environmental conditions may alter the relative costs and benefits of resistance and tolerance, thus maintaining genetic variation within goldenrod populations.